Are Free Government Health Services the Best Way to Reach to Poor? - Gwatkin, Davison R. (World Bank, Washington, DC, 2013)
The paper asks whether the pursuit of universal coverage by a wide range of free government services constitutes the most promising approach to meeting the needs of disadvantaged population groups. The response given to that question is probably not. The record to date points clearly to the danger that the benefits of subsidized government health services will flow primarily to the better-off, rather than to the poor for whom the services are intended. While there is no perfect approach to dealing with this issue, the record also points to several approaches that can significantly ameliorate the situation. Two of them, discussed in the paper, are the adoption of targeting measures to increase the proportion of benefits from government expenditures that flow to the poor; and the development of alternative, self-sustaining service financing and delivery mechanisms to serve the better-off. Successful implementation of approaches like these would allow governments to focus their efforts to achieve universal free coverage on a limited number of interventions that are particularly important for poor groups.